An Analytical Overview of Book Publishing and Copyright Issues in Pakistan - Muhammad Asif; Liu Yang; Majid Ali; Muhammad Hashim (International Journal of Instructional Technology and Educational Studies)
The research investigates the issues confronting the Pakistani book publishing sector since books are an efficient means of communication for rhetoric. A theoretical research approach was chosen, and secondary information was acquired by examining numerous relevant and genuine sources. The study has used functionalism and value change theory; it indicates that an individual should get accurate knowledge about the subject before modifying their values. Each subsystem is expected to contribute significantly to the society's continuity and orderly functioning. The book is necessary for the continued survival, progress, and advancement of civilization. Without any of the publishing sector, there would be no books. Book publication plays a vital role in every civilization since it allows for the spread and diffusion of information. It is a component of a knowledge distribution system. There have been issues confronting the Pakistani book publishing sector, such as poor reading culture, government regulation, piracy, Improper finance, and a lack of knowledge. The study suggests that stakeholders develop creative solutions that can meet the industry's people and material requirements. According to the investigation, stakeholders in the publishing sector should develop a healthy publishing industry. Private investors, such as financial institutions and influential people, should contribute significantly to the massive capital inflow. The government should begin developing strategies to reduce the issue of piracy and charge lower import tariffs on publishing appliances. The problem of book piracy is rooted in social, economic, scholarly, and legal factors.